Waves and instabilities in high quality adiabatic flow in microgap channels. (July 2016) - Bar-Cohen, Avram; Holloway, Caleb; Kaffel, Ahmed; Riaz, Amir
Highlights: Wave patterns are observed on the liquid-vapor interface in two-phase annular flow. Smooth, widely spaced 3D waves are observed at a mass flux of 220 kg/m 2 -s. "Scaly", tightly spaced 3D waves are observed at larger mass fluxes. The wavelength of interfacial waves decrease with flow quality and mass flux. Wavelengths are accurately predicted with a numerical linear stability analysis. Abstract: Two-phase flow in microgap channels offers highly potent thermal management capability and is the foundation for the emerging "embedded cooling" paradigm of electronic cooling. While heat transfer and pressure drop in such flows are intimately tied to their distinct forms of vapor–liquid aggregation, insufficient attention has been paid to characterizing the wave patterns and sub-regimes in high-quality microgap channel flow. The present visualization study focuses on two-phase flow in an adiabatic 184 μ m microgap channel operating at three mass fluxes of FC-72; 220, 420, and 620 kg/m 2 -s, with flow qualities ranging from approximately 40% to 90%. As predicted by a modified Taitel–Dukler flow regime map, annular flow is found to be the dominant flow regime for the present microgap configuration. Within the annular flow regime, unique 3-D wave patterns are observed at the liquid–vapor interface. The wavelength of these interfacial waves is observed to decrease with increasing flow quality and mass flux. Linear stability analysis of the liquid–vapor interface is found to yield strong agreement in predicted wavelength and wave growth rate distribution with the experimental results.